Development and Validation of a Procedure for Quantitative Determination of Flavonoids in Sea Buckthorn Leaves by Spectrophotometry - N. A. Kovaleva; O. V. Trineeva; I. V. Chuvikova; A. I. Slivkin (Регуляторные исследования и экспертиза лекарственных средств)
Sea buckthorn fruits are a pharmacopoeial raw material used to produce sea buckthorn oil. Other parts of the plant (bark, leaves, and shoots) are objects of research aiming to expand the raw material base and use limited natural resources rationally. Sea buckthorn leaves are rich in biologically active compounds, including flavonoids.The aim of the study was to develop and validate an analytical procedure for the quantification of flavonoids in sea buckthorn leaves using spectrophotometry in the visible spectral region.Materials and methods. The study focused on dried leaves of sea buckthorn harvested in the Voronezh region in 2022. These leaves were collected from wild plants at three phenological stages: fruit setting (I), single fruit ripening (II), and mass fruit ripening (III). To quantify flavonoids in sea buckthorn leaves, the authors used an analytical procedure based on measuring the absorbance of a solution containing products of the reaction between flavonoids and aluminium chloride.Results. The absorption maximum of the complex between the alcohol extract of sea buckthorn leaves and aluminium chloride was observed at 402±2 nm; the wavelength corresponds to the absorption maximum of luteolin. The optimal extraction conditions included 70% ethanol as the extraction solvent, a raw material to solvent ratio of 1:150, a particle size of 0.5 mm, and a single extraction cycle of 45 min.Conclusions. The authors developed and validated a spectrophotometric procedure for the quantification of total flavonoids, expressed as luteolin, in sea buckthorn leaves. The procedure can be used to standardise this herbal drug. As observed in the study, the total flavonoid content was the highest (up to 1.5%) in the raw material at phenological stage I (collected in mid-June) and gradually decreased through mid-July to the end of August. Since sea buckthorn is the source of sea buckthorn oil and the early collection of leaves may decrease its value or lead to non-compliance with pharmacopoeial requirements, the recommended time for harvesting leaves should coincide with that for harvesting fruits. Collected at this stage of growth and development, sea buckthorn leaves still contain sufficient flavonoids (up to 0.8%) and can be used as an individual herbal drug.